Assessing bias in total mercury results after removing a subsample from the bottle. Issue 11 (1st September 2016) - Creswell, Joel E.; Carter, Annie; Chen, Bin; DeWild, John; Fajon, Vesna; Rattonetti, Anthony; Saffari, Mark; Tsui, Martin Tsz-Ki; Živković, Igor; Braaten, Hans Fredrik Veiteberg
ABSTRACT: U.S. EPA Method 1631 for total mercury (THg) analysis in water recommends that bromine monochloride (BrCl) be added to the original bottle in which the sample was collected, to draw into solution any Hg that may have adsorbed to the bottle walls. The method also allows for the removal of a subsample of water from the sample bottle for methylmercury (MeHg) analysis prior to adding BrCl. We have demonstrated that the removal of a subsample from the sample bottle prior to THg analysis can result in a positive concentration bias. The proposed mechanism for the bias is that 'excess' inorganic Hg, derived from the subsample that was removed from the bottle, adsorbs to the bottle walls and is then drawn into solution when BrCl is added. To test for this bias, we conducted an interlaboratory comparison study in which nine laboratories analysed water samples in fluorinated polyethylene (FLPE) bottles for THg after removing a subsample from the sample bottle, and analysed a replicate sample bottle from which no subsample was removed. We received seven complete data sets, or 63 unique sample pairs. The positive concentration bias between the bottles was significant when comparing all samples in aggregate (1.76 ± 0.53 ng/L after subsample removal, 1.57 ± 0.58 ng/L with no subsample removal, P < 0.05), however when comparing each of the three samples individually, the only significant bias was in the saline sample (Site UJ; 1.51 ± 0.31 ng/L after subsample removal, 1.32 ± 0.47 ng/L with no subsample removal, P < 0.05). Based on the findings presented here, we conclude that water chemistry, volume of water poured off, and the sample storage temperature explain some but not all of the observed bias, and we recommend collecting THg and MeHg samples in separate bottles whenever possible.